Selection of a Single Domain Antibody, Specific for an HLA-Bound Epitope of the Mycobacterial Ag85B Antigen - Ortega, Paola A.; Silva-Miranda, Mayra; Torres-Larios, Alfredo; Campos-Chávez, Eduardo; Franken, Kees C. L. C. M.; Ottenhoff, Tom H. M.; Ivanyi, Juraj; Espitia, Clara (Frontiers in Immunology, 2020)
T cells recognizing epitopes on the surface of mycobacteria-infected macrophages can impart protection, but with associated risk for reactivation to lung pathology. We aimed to identify antibodies specific to such epitopes, which carry potentials for development toward novel therapeutic constructs. Since epitopes presented in the context of major histocompatibility complex alleles are rarely recognized by naturally produced antibodies, we used a phage display library for the identification of monoclonal human single domain antibody producing clones. The selected 2C clone displayed T cell receptor-like recognition of an HLA-A*0201 bound 199KLVANNTRL207 peptide from the Ag85B antigen, which is known to be an immunodominant epitope for human T cells. The specificity of the selected domain antibody was demonstrated by solid phase immunoassay and by immunofluorescent surface staining of peptide loaded cells of the T2 cell line. The antibody affinity binding was determined by biolayer interferometry. Our results validated the used technologies as suitable for the generation of antibodies against epitopes on the surface of Mycobacterium tuberculosis infected cells. The potential approaches forward the development of antibody in immunotherapy of tuberculosis have been outlined in the discussion.